No gold standard estimation of the sensitivity and specificity of two molecular diagnostic protocols for Trypanosoma brucei spp. in Western Kenya - Bronsvoort, B.M. de C.; Wissmann, B. von; Fèvre, Eric M.; Handel, Ian G.; Picozzi, K.; Welburn, S.C. (Public Library of Science, 2010)
African animal trypanosomiasis is caused by a range of tsetse transmitted protozoan parasites includingTrypanosoma vivax, Trypanosoma congolense and Trypansoma brucei. In Western Kenya and other parts of East Africa two subspecies of T. brucei, T.b. brucei and the zoonoticT.b. rhodesiense, co-circulate in livestock. A range of polymerase chain reactions (PCR) have been developed as important molecular diagnostic tools for epidemiological investigations of T. brucei s.l. in the animal reservoir and of its zoonotic potential. Quantification of the relative performance of different diagnostic PCRs is essential to ensure comparability of studies. This paper describes an evaluation of two diagnostic test systems for T. brucei using a T. brucei s.l. specific PCR [1] and a single nested PCR targeting the Internal Transcribed Spacer (ITS) regions of trypanosome ribosomal DNA [2]. A Bayesian formulation of the Hui-Walter latent class model was employed to estimate their test performance in the absence of a gold standard test for detecting T.brucei s.l. infections in ear-vein blood samples from cattle, pig, sheep and goat populations in Western Kenya, stored on Whatman FTA cards. The results indicate that the system employing the T. brucei s.l. specific PCR (Se1 = 0.760) had a higher sensitivity than the ITS-PCR (Se2 = 0.640); both have high specificity (Sp1 = 0.998; Sp2 = 0.997). The true prevalences for livestock populations were estimated (pcattle = 0.091, ppigs = 0.066, pgoats = 0.005, psheep = 0.006), taking into account the uncertainties in the specificity and sensitivity of the two test systems. Implications of test performance include the required survey sample size; due to its higher sensitivity and specificity, the T. brucei s.l. specific PCR requires a consistently smaller sample size than the ITS-PCR for the detection of T. brucei s.l. However the ITS-PCR is able to simultaneously screen samples for other pathogenic trypanosomes and may thus be, overall, a better choice of test in multi-organism studies.